1996
DOI: 10.1093/njaf/13.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating a Young Northern Red Oak Planting with Tree Shelters

Abstract: Methods for deer browse protection are becoming a necessary aspect of hardwood silviculture, particularly with practices such as artificial regeneration of oaks. This study tested the effectiveness of two types of deer protection for aiding the rehabilitation of a failed northern red oak planting in southern Indiana. Tree shelters, bar soap repellent, and no protection (control) treatments were applied to 1 yr old, coppice-origin oak shoots arising from 8 yr old root-stocks of an unsuccessful 1980 old-field re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Height of N. dombeyi seedlings was not affected by the use of tree shelters neither in the xeric site, and nor in the mesic site, at least until the second growing season (prior to the browsing effect). This result contrasted with those of several hardwood (Davies 1985;Tuley 1985;Gillespie et al 1996;Bendfeldt et al 2001;McCreary and Tecklin 2001;Dorji et al 2020) and conifer species (Ward et al 2000;Jacobs 2011), which had shown a pronounced positive impact on height with the use of tree shelters. It seems that our results agree with those of the authors who indicate that the net effect of tree shelters on plant growth appeared to be site-and/or species-dependent (Frearson and Weiss 1987;Potter 1988;Burger et al 1992;Buresti and Sestini 1994;Ward and Stephens 1995;West et al 1999;Ponder 2003;Famiani et al 2007;Puértolas et al 2010;Oliet and Jacobs 2007;Piñeiro et al 2013).…”
Section: Tree Shelters and Neighboring Vegetation Effects On Growthcontrasting
confidence: 67%
“…Height of N. dombeyi seedlings was not affected by the use of tree shelters neither in the xeric site, and nor in the mesic site, at least until the second growing season (prior to the browsing effect). This result contrasted with those of several hardwood (Davies 1985;Tuley 1985;Gillespie et al 1996;Bendfeldt et al 2001;McCreary and Tecklin 2001;Dorji et al 2020) and conifer species (Ward et al 2000;Jacobs 2011), which had shown a pronounced positive impact on height with the use of tree shelters. It seems that our results agree with those of the authors who indicate that the net effect of tree shelters on plant growth appeared to be site-and/or species-dependent (Frearson and Weiss 1987;Potter 1988;Burger et al 1992;Buresti and Sestini 1994;Ward and Stephens 1995;West et al 1999;Ponder 2003;Famiani et al 2007;Puértolas et al 2010;Oliet and Jacobs 2007;Piñeiro et al 2013).…”
Section: Tree Shelters and Neighboring Vegetation Effects On Growthcontrasting
confidence: 67%
“…This increased height growth produced seedlings that were significantly more slender (i.e., greater H:D). This phenomenon has been attributed to lack of stem movement inside solid‐walled shelters (Kjelgren & Rupp 1997; Johansson 2004) and etiolation due to the reduction in light (Gillespie et al 1996). Once oak seedlings grow beyond the top of tree shelters, there is a significant increase in stem diameter growth rate accompanied by a decrease in height growth rate, resulting in a sturdier stem (McCreary & Tecklin 2001).…”
Section: Discussionmentioning
confidence: 99%